Upaya Perlindungan Benda Cagar Budaya Lawang Sewu Semarang - Dwi Haryadi (KEADILAN PROGRESIF, 2011)
Indonesia has many ancient buildings spread inÂ  almos regions. One of them is Lawang Sewu in Semarang. The position is very strategic because it is located on Jalan Pemuda precisely on the right side of Tugu Muda. Howevetr, its position as a sanctuary protected by Law as well as an inheritance of previous history is not in tune with the concerned condition and ,he preservation and protection efforts. The protection eforts of lawang sewu as cultule security thing in this time not yet done according lo maximal, either by Semarang city government or PT.KAI DAOP IV Semarang as owner The protection of lawang sewu also doesnt quit Jrom many factors: the minimum estimation, private investor not interest: The government wisdoms not yet to maximal application in culture security preservation; and still the weak pacificalion and law enforcement.